ASEAN: overcoming the continental-maritime divide - Kwa, Chong Guan (2023)
The expansion of ASEAN (Association of Southeast Asian Nations) in the 1990s brought together its founding members, a group of countries located in the maritime world of Southeast Asia, with the other countries on the mainland of the region centred around the major river systems (notably the Irrawaddy and Mekong). The growth of ASEAN conjoined two sets of modern states with divergent socio-cultural upbringing and geopolitical visions: one dependent on the seas around it and the other on the great rivers and their headwaters upon which their livelihood depended. ASEAN’s disunity and indecisiveness on critical issues it faces in the South China Sea and major power competition in the region is in part a consequence of this geographical reality.